2009
DOI: 10.1097/mcp.0b013e32832a0adc
|View full text |Cite
|
Sign up to set email alerts
|

T-cell interferon-γ release assays for the rapid immunodiagnosis of tuberculosis: clinical utility in high-burden vs. low-burden settings

Abstract: IGRAs may still be useful in high-burden settings in specific subgroups at high risk of progression, including young children, HIV-infected individuals and healthcare workers, but this requires confirmation. Although the IGRAs cannot distinguish between latent and active TB, their utility as rule-out tests, when combined with smear microscopy or the TST, requires further study. Prospective studies are required in high-burden settings to confirm whether IFN-gamma responses are predictive of high risk of progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
157
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(164 citation statements)
references
References 123 publications
3
157
1
3
Order By: Relevance
“…For the T-SPOT.TB assay, the sensitivity was between 79 and 95% and the specificity was between 64% and 100% for active TB in HIV-infected patients (74). The sensitivity of the QFT-GIT test for culture-confirmed pulmonary TB in HIV-infected patients ranged from 65% to 91% in previously reported studies, and the likelihood of indeterminate results increased with lower CD4 counts (1,9,74,158,177,242,254). Aabye et al found that 22% of HIV-infected patients with culture-confirmed pulmonary TB had indeterminate results with the QFT-GIT test, and patients with CD4 counts below 300 cells/l were nearly 3 times as likely to have indeterminate results as patients with CD4 counts above 300 cells/l (1).…”
Section: Ifn-␥ Release Assays For Hiv-infected Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the T-SPOT.TB assay, the sensitivity was between 79 and 95% and the specificity was between 64% and 100% for active TB in HIV-infected patients (74). The sensitivity of the QFT-GIT test for culture-confirmed pulmonary TB in HIV-infected patients ranged from 65% to 91% in previously reported studies, and the likelihood of indeterminate results increased with lower CD4 counts (1,9,74,158,177,242,254). Aabye et al found that 22% of HIV-infected patients with culture-confirmed pulmonary TB had indeterminate results with the QFT-GIT test, and patients with CD4 counts below 300 cells/l were nearly 3 times as likely to have indeterminate results as patients with CD4 counts above 300 cells/l (1).…”
Section: Ifn-␥ Release Assays For Hiv-infected Patientsmentioning
confidence: 99%
“…These assays detect the release of the cytokine gamma interferon (IFN-␥) from T lymphocytes after stimulation with the M. tuberculosis-specific antigens early secretory antigen target 6 (ESAT-6) and culture filtrate protein 10 (CFP-10) and also TB antigen TB 7.7 for the QFT-GIT test (24,74). The QuantiFERON assays use anticoagulated whole blood and measure the release of gamma interferon into the supernatant by enzyme-linked immunosorbent assays (ELISAs), while the T-SPOT.TB assay uses isolated blood mononuclear cells and determines the number of gamma interferon-secreting cells in the sample by using an enzymelinked immunospot (ELISPOT) technique (24,74). Each test is performed with a negative control and a positive control, and results are reported as being indeterminate if there is a high signal for the negative control or a low signal for the positive control.…”
Section: Ifn-␥ Release Assays For Hiv-infected Patientsmentioning
confidence: 99%
“…These newer tests enumerate the frequency of peripheral blood effector T cells driven by RD-1 TB-specific antigens (early secreted antigenic target 6 [ESAT-6] and culture filtrate protein 10 [CFP-10]) (15,16). However, this blood-based immunologic approach is unsuitable for the diagnosis of active TB because the test cannot distinguish effector cells in the context of LTBI from cells present during active disease (17)(18)(19)(20)(21).…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
“…More recently, rapid immunodiagnostic tests, using peripheral whole blood or mononuclear cells, for the diagnosis of latent TB infection (LTBI) have become commercially available (15). These newer tests enumerate the frequency of peripheral blood effector T cells driven by RD-1 TB-specific antigens (early secreted antigenic target 6 [ESAT-6] and culture filtrate protein 10 [CFP-10]) (15,16).…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
“…[3][4][5][6] The best example of cytokine production being used for diagnostics is the detection of tuberculosis (TB) where production of a cytokine-interferon (IFN)-c-is currently used as a diagnostic of latent TB disease. [7][8][9] The so called IFN-c release assays (IGRAs) are based on detecting cytokine production from TB-specific T-cells and are rapidly supplanting tuberculin skin tests. IGRAs are immunoassays that either quantify levels of IFN-c production by enzyme linked immunosorbent assay (ELISA) or count cytokine-producing cells.…”
Section: Introductionmentioning
confidence: 99%